Social issues in amazon waters: senses, perceptions and representations - Agra, Klondy Lúcia de Oliveira (Acta Scientiarum. Human and Social Sciences, 2017)
With the main objective of observing as the senses are constituted in Amazonian communities, the perception of the subjects and their social representations about the importance, the use and preservation of water to know the logic of these communities, social and problematic phenomena that surround it, a qualitative research was conducted under the theoretical framework of the Cultural Geography. The spatial area of this study consists of six (06) communities inserted in two cities of the State of Rondônia: Porto Velho and Guajará-Mirim. With the help of Human Geography in its phenomenological perspective, whose interface permeated the Sociocultural Geography, it was observed that Amazonian communities exposed intimate senses in relation to waters that constitute their identities and, through these senses, identified the connections between social phenomena and problems surrounding their water, their world lived.